2020
DOI: 10.1021/acsami.9b22060
|View full text |Cite
|
Sign up to set email alerts
|

Imidazo[1,2-b]pyridazine as Building Blocks for Host Materials for High-Performance Red-Phosphorescent Organic Light-Emitting Devices

Abstract: A novel electron-transporting unit, imidazo [1,2-b]pyridazine (IP), was first reported for developing host materials. The IP moiety possesses excellent electron-transporting ability and great thermal stability. Using carbazole as p-type units and IP as n-type units, several bipolar host materials, namely, IP6Cz, IP68Cz, IP36Cz, and IP368Cz, were developed through altering the substitution site of the IP core. Among these four materials, 6-site-substituted IP6Cz and 6,8-sitesubstituted IP68Cz exhibit the best e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…This new series of host materials 54-57 for high-performance red phosphorescent organic light-emitting devices was prepared using Suzuki-Miyaura cross-coupling method (scheme 27). [101] The reactions were performed employing Pd(PPh 3 ) 4 as catalyst with (9-phenyl-9H-carbazol-3-yl)boronic acid and specific halogenated imidazo[1,2-b]pyridazines 53(a-d) in the presence of K 2 CO 3 in THF/H 2 O at reflux for 24 h. The arylated imidazo[1,2-b]pyridazines 54-57 were obtained in good yields (scheme 27).…”
Section: Suzuki-miyaura Cross-couplingmentioning
confidence: 99%
“…This new series of host materials 54-57 for high-performance red phosphorescent organic light-emitting devices was prepared using Suzuki-Miyaura cross-coupling method (scheme 27). [101] The reactions were performed employing Pd(PPh 3 ) 4 as catalyst with (9-phenyl-9H-carbazol-3-yl)boronic acid and specific halogenated imidazo[1,2-b]pyridazines 53(a-d) in the presence of K 2 CO 3 in THF/H 2 O at reflux for 24 h. The arylated imidazo[1,2-b]pyridazines 54-57 were obtained in good yields (scheme 27).…”
Section: Suzuki-miyaura Cross-couplingmentioning
confidence: 99%
“…Chart 1: Selected examples of state of the art of heteroatoms-based host materials. [4][5][6][7][8][9][10] Second, regarding the stability, it has been shown that the C-N, C-P and C-S bonds, particularly in their excited states, can be easily broken by the energy of excitons formed in blue PhOLEDs (which is around 3 eV). [31][32][33] Indeed, the dissociation energies of the C-N, C-P or C-S bonds in common building units used in host materials lies in this range.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] To suppress exciton annihilation and concentration quenching in emitting layers, generally, these triplet-excited-state-involved emitters have to be doped into suitable host materials. [6][7][8][9][10][11] The triplet energy of the host must be higher than that of the emitter to ensure efficient exothermic energy transfer from the host to the guest molecule and to confine the triplet excitons within the emitting layers. [12][13][14] In the case of blue emitters, the lowest triplet state (T 1 ) energy level of the host should be at least 2.9 eV.…”
Section: Introductionmentioning
confidence: 99%